Deep Sidhu, Kisan Morcha and the erasure of Sikh suffering in the liberal imagination. (3rd April 2022) - Singh, Prabhsharanbir
ABSTRACT: This article explores the ideological roots of the tension between the Sikhs and the left organizations of Punjab in the context of Kisan Morcha . During the year-long protest movement, Deep Sidhu became the focal point of this tension. This article argues that the roots of this tension are far deeper than is commonly realized. The process of modernization and psychic McDonaldization that resulted from it, are the driving forces behind this tension. Deep Sidhu represented the singularity of Sikhi and Punjab that resisted this global drive towards uniformity. However, his death also sparked a new political consciousness.